Design of a Single Expansion Ramp Nozzle and Numerical Investigation of Operation at OverExpanded Conditions - Magalhães, Jorge Filipe Suadate Correia de (2022)
In the present thesis, a single expansion ramp nozzle (SERN) is designed and investigated. A Python algorithm based on the method of characteristics (MOC) is developed, which generates the optimised contour of a 2D supersonic calorically perfect minimum length nozzle (MLN), for ideal shockfree flow expansion, and calculates various flowfield properties within the nozzle. The algorithm results shows good agreement with theoretical background, previous literature and CFD simulations, thus validating the code. An optimised SERN geometry is then designed using the algorithm, operating with an exit Mach number of ME = 4 and a specific heat ratio of ? = 1.4. The optimal geometry is truncated at 40% of its length for viable integration into a vehicle, without significant loss in thrust. A numerical framework is created in ANSYS FLUENT 16.2, and validated by comparison with data from previous experimental investigations conducted on SERN’s. The validated model is then applied to the SERN designed in this study, where various simulations of design and offdesign conditions are conducted. The numerical simulations are solved in a steadystate 2D environment, using the densitybased solver and the k - e RNG turbulence model. Case A simulates SERN operation at design altitude (22 km) and speed (Mach 4), through nozzle pressure ratios (NPR’s) 133.65 (design), 100, 75, 50 and 25. Near perfect expansion of the gases is achieved at the design NPR. As the NPR is reduced, the flow becomes overexpanded, with the formation of incident shockwaves at the nozzle exit and reflected shockwaves further downstream, reduction of exhaust flow speed and contraction of the exhaust plume. From NPR = 133.65 to NPR = 25, the SERN’s thrust, lift and moments suffer a linear reduction of 81.33%, 80.7% and 81.17%, respectively. Case B simulates SERN operation at offdesign speed (Mach 0.4) and altitude (8 km), through NPR’s 4, 5, 6, 8, 10, 12, 15 and 20. Severe overexpanded flow and complex shockwave patterns are observed, such as the restricted shock separation (RSS) pattern, including separation and reattachment of the main jet to the ramp, formation of a separation bubble on the ramp, a large recirculation region on the flap, Mach disks, ? shock structures and shocktrains. From NPR = 4 to NPR = 20, the SERN’s thrust, lift and moments varied to some degree, with an overall increase of 38.2%, 5.27% and 42.3% respectively.